KONSEP PENDIDIKAN MENURUT AL-QUR’AN HADIS - Murjani Murjani (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
This research is a literature review, in which the results of the study found that; First, the concept of terbiyah, tazkiyah and ta'dib is a complete unit within the framework of building Islamic education. Tarbiyah contains the content of conscious efforts to maintain, develop all human potential in accordance with their nature and comprehensive protection of their human rights. Meanwhile, tazkiyah cleanses the soul of despicable qualities and fills it with commendable qualities. Ta'dib is a process of developing personality and moral (affective) and ethical attitudes in life. Second, Tarbiyah, tazkiyah and ta'dib essentially both refer to the maintenance, protection and development of the overall potential of human beings towards human perfection itself (insan al-kamil). Therefore, in its application these three things must be able to work together to achieve the goals of Islamic education.